Nanomaterials to combat SARS-CoV-2: Strategies to prevent, diagnose and treat COVID-19 - Valenzuela-Fernández, Agustín; Cabrera-Rodriguez, Romina; Ciuffreda, Laura; Perez-Yanes, Silvia; Estevez-Herrera, Judith; González-Montelongo, Rafaela; Alcoba-Florez, Julia; Trujillo-González, Rodrigo; García-Martínez de Artola, Diego; Gil-Campesino, Helena; Díez-Gil, Oscar; Lorenzo-Salazar, José M.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the associated coronavirus disease 2019 (COVID-19), which severely affect the respiratory system and several organs and tissues, and may lead to death, have shown how science can respond when challenged by a global emergency, offering as a response a myriad of rapid technological developments. Development of vaccines at lightning speed is one of them. SARS-CoV-2 outbreaks have stressed healthcare systems, questioning patients care by using standard non-adapted therapies and diagnostic tools. In this scenario, nanotechnology has offered new tools, techniques and opportunities for prevention, for rapid, accurate and sensitive diagnosis and treatment of COVID-19. In this review, we focus on the nanotechnological applications and nano-based materials (i.e., personal protective equipment) to combat SARS-CoV-2 transmission, infection, organ damage and for the development of new tools for virosurveillance, diagnose and immune protection by mRNA and other nano-based vaccines. All the nano-based developed tools have allowed a historical, unprecedented, real time epidemiological surveillance and diagnosis of SARS-CoV-2 infection, at community and international levels. The nano-based technology has help to predict and detect how this Sarbecovirus is mutating and the severity of the associated COVID-19 disease, thereby assisting the administration and public health services to make decisions and measures for preparedness against the emerging variants of SARS-CoV-2 and severe or lethal COVID-19.